Characterization of the hemoglobins and globins of Synbranchus marmoratus Bloch, 1795 (Pisces, Synbranchidae) - Nakamoto, Wilson [UNESP]; Machado, Paulo Eduardo de Abreu [UNESP] (Elsevier B.V., 1986)
1. 1. Total hemolysates of Synbranchus marmoratus Bloch, 1795, captured in Vitoriana, district of Botucatu, State of São Paulo, Brazil, were submitted to agar-starch gel electrophoresis on glass slides using 42 mM-Tris 1.7 mM EDTA-6.1 mM borate buffer, pH 8.8, for the gel and 10 mM borate-1.7 mM NaOH buffer, pH 8.6, for the cuvette. 2. 2. Three distinct hemoglobin bands were detected, with Hb I being of the cathodic type. 3. 3. Cellulose acetate electrophoresis in 800 mM Tris-2.1 mM EDTA buffer, pH 8.9, containing 6 M urea and 2.25 mM β-mercaptoethanol indicated the presence of four globin chains denoted α 1, α 2, β and γ. 4. 4. It is suggested that the probable tetrameric constitution of the hemoglobin of Synbranchus marmoratus Bloch, 1795 is Hb I (α 2 2γ 2), Hb II (α 2 1γ 2) and Hb III (α 2 1β 2). © 1986.
Keywords: Globin; Hemoglobin; Agar gel electrophoresis; Animal; Blood; Electrophoresis; Fish; Ion exchange chromatography; Animal; Chromatography, DEAE-Cellulose; Electrophoresis, Agar Gel; Electrophoresis, Cellulose Acetate; Fishes; Globins; Hemoglobins